The Rice Qa-SNAREs in SYP13 Subfamily Are Involved in Regulating Arbuscular Mycorrhizal Symbiosis and Seed Fertility - Liu, Ying-Na; Liu, Cheng-Chen; Guo, Rui; Tian, Li; Cheng, Jian-Fei; Wu, Ya-Nan; Wang, Dong; Wang, Bin (Frontiers in Plant Science, 2022)
Qa-SNARE gene SYP132 (isoform α) was previously reported to affect arbuscular mycorrhizal (AM) symbiosis in the legume species Medicago truncatula. In non-legumes especially monocots, it remains unknown whether certain SNARE genes are also involved in AM symbiosis. In this work, we studied a rice orthologous gene OsSYP132, which showed induced expression in mycorrhizal roots and two paralogous genes OsSYP131a and OsSYP131b, which were not induced by the AM fungus Rhizophagus irregularis. After employing CRISPR/Cas9 technique to generate their mutants, the Ossyp131a homozygous mutant T0 plants exhibited a dwarf phenotype and produced no fertile seeds, indicating a required role of this gene in seed fertility. Unlike the case in legume, the Ossyp132 mutants exhibited normal mycorrhizal phenotype, so did the Ossyp131b mutants. In the Ossyp131b Ossyp132 double mutants, however, the colonization rate and arbuscule abundance level decreased markedly, indicating an impaired fungal proliferation ability in rice roots. Such a defect was further confirmed by the reduced expression levels of AM marker genes. Our results in rice therefore demonstrated that while SYP13II members showed evolutionary and induction patterns specific to symbiosis, AM symbiosis is in fact controlled by the combined action of both SYP13I and SYP13II clades, revealing a functional redundancy among SYNTAXIN genes in mutualism.